Gut Microbiota Cannot Compensate the Impact of (quasi) Aposymbiosis in Blattella germanica - Muñoz-Benavent, Maria; Latorre, Amparo; Alemany-Cosme, Ester; Marín-Miret, Jesús; Domínguez-Santos, Rebeca; Silva, Francisco J.; Gil, Rosario; García-Ferris, Carlos (Biology (Basel, Switzerland), 2021)
Blattella germanica presents a very complex symbiotic system, involving the following two kinds of symbionts: the endosymbiont Blattabacterium and the gut microbiota. Although the role of the endosymbiont has been fully elucidated, the function of the gut microbiota remains unclear. The study of the gut microbiota will benefit from the availability of insects deprived of Blattabacterium. Our goal is to determine the effect of the removal (or, at least, the reduction) of the endosymbiont population on the cockroach’s fitness, in a normal gut microbiota community. For this purpose, we treated our cockroach population, over several generations, with rifampicin, an antibiotic that only affects the endosymbiont during its extracellular phase, and decreases its amount in the following generation. As rifampicin also affects gut bacteria that are sensitive to this antibiotic, the treatment was performed during the first 12 days of the adult stage, which is the period when the endosymbiont infects the oocytes and lacks bacteriocyte protection. We found that after this antibiotic treatment, the endosymbiont population remained extremely reduced and only the microbiota was able to recover, although it could not compensate for the endosymbiont role, and the host’s fitness was drastically affected. This accomplished reduction, however, is not homogenous and requires further study to develop stable quasi-aposymbiotic cockroaches.